2016
DOI: 10.1294/jes.27.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a joint supplement whose main components are resveratrol and hyaluronic acid on some biochemical parameters in aged lame horses

Abstract: This study aimed to evaluate the effects of a supplement that contains resveratrol and hyaluronic acid (RH supplement) in aged lame horses. A total of 16 horses of both sexes, aged between 15 and 22 years, weighing between 350–450 kg and showing lameness due to arthritis of the knee, hock, stifle, and fetlock joints and stiffness owing to ageing were used for the study. They comprised eight horses that were administered the RH supplement for three weeks and eight others that served as controls and were given o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is possible that the dose of resveratrol administered to horses in this study (450 mg twice daily) was not sufficient to exert an immunomodulatory effect on the measured parameters. All other in vivo equine studies employed a different commercially available resveratrol supplement, and the total dose per day was somewhat higher compared to the manufacturer's recommendations for the supplement used in our study [23][24][25][26][27][28][29]. The formulation of the resveratrol supplement might be a contributing factor to effect (or lack thereof) because of the poor solubility and bioavailability of resveratrol, creating a major challenge for the pharmaceutical industry [36].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is possible that the dose of resveratrol administered to horses in this study (450 mg twice daily) was not sufficient to exert an immunomodulatory effect on the measured parameters. All other in vivo equine studies employed a different commercially available resveratrol supplement, and the total dose per day was somewhat higher compared to the manufacturer's recommendations for the supplement used in our study [23][24][25][26][27][28][29]. The formulation of the resveratrol supplement might be a contributing factor to effect (or lack thereof) because of the poor solubility and bioavailability of resveratrol, creating a major challenge for the pharmaceutical industry [36].…”
Section: Discussionmentioning
confidence: 92%
“…Although the use of resveratrol as a nutraceutical with numerous purported but unproven benefits for equine health has been gaining acceptance in recent years, published studies reporting anti-inflammatory or analgesic effects in horses are few [23][24][25][26][27][28][29]. In one study of performance horses affected with distal tarsitis, oral resveratrol supplementation used in conjunction with an intra-articular corticosteroid resulted in reduced lameness when compared to intra-articular corticosteroid and an orally administered placebo [28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Ememe et al [82], showed a significant reduction in values of creatine kinase and glucose in the horses administered resveratrol and hyaluronic acid (equithrive joint ® ) (Figure 3) supplement. Elevated levels of these substances have been associated with a reduction in metabolic efficiency in aging animals.…”
Section: Resveratrol Studies In Horsesmentioning
confidence: 88%
“…There are many studies describing different mechanisms by which resveratrol decreased the cholesterol concentration in blood, e.g., by reducing the basal and insulin-induced glucose conversion to total lipids in white adipose tissue [55]. There are also studies which found no effect of resveratrol on cholesterol concentration in horse blood [30]. Again, it seems that different active compounds are behind these diverse effects of knotweed.…”
Section: Cholesterolmentioning
confidence: 99%
“…Metabolic efficiency in animals decreases with age, leading to increased levels of creatine kinase and glucose. A decrease in both creatine kinase and glucose levels in horses receiving resveratrol and hyaluronic acid (EquithriveJoint ® ) was found [30]. EquithriveJoint ® was administered to old, lame horses and a decreased serum malondialdehyde (MDA) concentration and modulated serum levels of glutathionperoxidase (GPx), catalase and superoxiddismutase (SOD) were found, indicating protective effects of EquithriveJoint ® against oxidative stress and ageing [31].…”
Section: Introductionmentioning
confidence: 99%